Kodifikasi Sunah (Telaah Historis Mulai Abad I Sampai Abad III H): Codification of the Sunnah (Historical Study from the 1st to 3rd Century of Hijri) - Sudahnan, Lukmanul Hakim (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2024)
This research aims to explain the codification of the Sunnah and its phases and describe the methodology in each phase, from the time of the companions of the Prophet Sallallaahu ‘alaihi wasallam until the third century of the Hijri. This research focuses on the first century because these three centuries were the most important moments related to recording, bookkeeping, and compiling hadith books, especially in the first century; many people doubt that there was any hadith recording activity at that time and that hadith were only oral traditions which were then memorized by the companions of the Prophet as if there was no physical evidence in the form of hadith records that showed the authenticity of the Prophet's hadith. This conclusion has the potential to become an obscurity that could weaken belief in the originality of the hadith, therefore making this research very urgent. This research uses a qualitative approach and literature study methodology, combining Arabic and Indonesian language references. The results of the research show that: (1) in the time of the Prophet's Companions, there was no codification of hadith, but the process of recording hadith was carried out by some of the companions; (2) the codification of hadith was carried out during the time of the caliph Omar ibn Abdu al-Aziz at the end of the first century and the beginning of the second century; (3) the process of codifying hadith was transformed into a thematic and systematic compilation of hadith books, and this began in the middle of the second century.